Increased titer and reduced lactate accumulation in recombinant retrovirus production through the down‐regulation of HIF1 and PDK. Issue 1 (2nd September 2015) - Rodrigues, A. F.; Guerreiro, M. R.; Formas‐Oliveira, A. S.; Fernandes, P.; Blechert, A.‐K.; Genzel, Y.; Alves, P. M.; Hu, W. S.; Coroadinha, A. S.
ABSTRACT: Many mammalian cell lines used in the manufacturing of biopharmaceuticals exhibit high glycolytic flux predominantly channeled to the production of lactate. The accumulation of lactate in culture reduces cell viability and may also decrease product quality. In this work, we engineered a HEK 293 derived cell line producing a recombinant gene therapy retroviral vector, by down‐regulating hypoxia inducible factor 1 ( HIF1 ) and pyruvate dehydrogenase kinase ( PDK ). Specific productivity of infectious viral titers could be increased more than 20‐fold for single gene knock‐down ( HIF1 or PDK ) and more than 30‐fold under combined down‐regulation. Lactate production was reduced up to 4‐fold. However, the reduction in lactate production, alone, was not sufficient to enhance the titer: high‐titer clones also showed significant enrolment of metabolic routes not related to lactate production. Transcriptome analysis indicated activation of biological amines metabolism, detoxification routes, including glutathione metabolism, pentose phosphate pathway, glycogen biosynthesis and amino acid catabolism. The latter were validated by enzyme activity assays and metabolite profiling, respectively. High‐titer clones also presented substantially increased transcript levels of the viral genes expression cassettes. The results herein presented demonstrate the impact of HIF1 and PDK down‐regulation on the production performance of a mammalian cell line, reporting one of the highest fold‐increase in specific productivity of infectious virus titers achieved by metabolic engineering. They additionally highlight the contribution of secondary pathways, beyond those related to lactate production, that can be also explored to pursue improved metabolic status favoring a high‐producing phenotype. Biotechnol. Bioeng. 2016;113: 150–162. © 2015 Wiley Periodicals, Inc. Abstract : In this study, Rodrigues et al. engineered HEK 293 derived cells stably producing recombinant retrovirus to down‐regulate HIF1 and PDK, aiming at reducing lactate accumulation and enhancing the channeling of the glycolytic intermediates into TCA cycle, ultimately seeking for improved infectious viral titers. Specific productivity of infectious viral titers could be increased more than 20‐fold for single gene knock‐down ( HIF1 or PDK ) and more than 30‐fold under combined down‐regulation. Lactate production was reduced up to 4‐fold. High‐titer clones also showed significant enrolment of metabolic routes not related to lactate production as well as substantial amplification of the viral genes expression.